2017
DOI: 10.1096/fj.201700010r
|View full text |Cite
|
Sign up to set email alerts
|

Bimgene dosage is critical in modulating nephron progenitor survival in the absence of microRNAs during kidney development

Abstract: Low nephron endowment at birth has been associated with an increased risk for developing hypertension and chronic kidney disease. We demonstrated in an earlier study that conditional deletion of the microRNA (miRNA)-processing enzyme Dicer from nephron progenitors results in premature depletion of the progenitors and increased expression of the proapoptotic protein Bim (also known as Bcl-2L11). In this study, we generated a compound mouse model with conditional deletion of both and, to determine the biologic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 106 publications
1
16
0
Order By: Relevance
“…Samples were immunostained with anti-Wt1 (1:100; Cell Signaling Technologies), and visualized using a Vectastain ABC Kit (Vector Laboratories). 32 Every 20 sections, Wt1 + structures were identified from consecutive sections using a Zeiss Model Axio Imager M1 (Zeiss) microscope with Stereo Investigator Stereology image tracing software (MBF Bioscience). Glomerular number was quantified using the equation by Cullen-McEwen et al 30 Serum Analysis P21 mice were anesthetized and subject to cardiac puncture for blood collection.…”
Section: Quantification Of P1 Nephron Numbermentioning
confidence: 99%
See 3 more Smart Citations
“…Samples were immunostained with anti-Wt1 (1:100; Cell Signaling Technologies), and visualized using a Vectastain ABC Kit (Vector Laboratories). 32 Every 20 sections, Wt1 + structures were identified from consecutive sections using a Zeiss Model Axio Imager M1 (Zeiss) microscope with Stereo Investigator Stereology image tracing software (MBF Bioscience). Glomerular number was quantified using the equation by Cullen-McEwen et al 30 Serum Analysis P21 mice were anesthetized and subject to cardiac puncture for blood collection.…”
Section: Quantification Of P1 Nephron Numbermentioning
confidence: 99%
“…E13.5 kidneys were cultured on 0.4 mm polyethylene terephthalate membrane inserts as previously described. 32 One kidney from each embryo was cultured in improved minimal essential media (containing 50 mg/ml transferrin) alone and the other was cultured in media containing 10 mM YN1 inhibitor. 22,32 After 72 hours kidneys were fixed in 4% paraformaldehyde for 1 hour.…”
Section: Kidney Explantsmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNAs are small, endogenous non‐coding RNAs (~22 nucleotides long) that primarily fine‐tune gene expression post‐transcriptionally to regulate various biological processes . Recent studies have identified miRNAs as important regulators of kidney development, particularly as inhibitors of nephron progenitor apoptosis . microRNA‐210‐3p ( miR‐210 ) is the most commonly induced hypoxia‐sensitive miRNA .…”
Section: Introductionmentioning
confidence: 99%